2014
DOI: 10.3389/fnhum.2014.00228
|View full text |Cite
|
Sign up to set email alerts
|

Language in the brain at rest: new insights from resting state data and graph theoretical analysis

Abstract: In humans, the most obvious functional lateralization is the specialization of the left hemisphere for language. Therefore, the involvement of the right hemisphere in language is one of the most remarkable findings during the last two decades of fMRI research. However, the importance of this finding continues to be underestimated. We examined the interaction between the two hemispheres and also the role of the right hemisphere in language. From two seeds representing Broca's area, we conducted a seed correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
45
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 66 publications
(116 reference statements)
9
45
1
Order By: Relevance
“…Another region that tends to be recruited during language tasks in both neurotypical participants (Binder, 1997) and participants with hemispherectomy (Liégeois et al, 2008) is the middle temporal gyrus; however, exploratory analyses of functional connectivity of the middle temporal gyrus in control participants revealed a network that included several brain regions not specific to language function, so it was not considered further. We verified that the ICN obtained from our seed in the right IFG was indeed the putative language ICN by qualitatively comparing it with (a) the networks described in the literature (e.g., Muller & Meyer, 2014), (b) the Neurosynth map corresponding to the term “language” (Yarkoni et al, 2011), and (c) a language ICN in control participants, obtained by placing a seed ROI within the left IFG (MNI coordinates −53 20 15).…”
Section: Methodssupporting
confidence: 62%
See 3 more Smart Citations
“…Another region that tends to be recruited during language tasks in both neurotypical participants (Binder, 1997) and participants with hemispherectomy (Liégeois et al, 2008) is the middle temporal gyrus; however, exploratory analyses of functional connectivity of the middle temporal gyrus in control participants revealed a network that included several brain regions not specific to language function, so it was not considered further. We verified that the ICN obtained from our seed in the right IFG was indeed the putative language ICN by qualitatively comparing it with (a) the networks described in the literature (e.g., Muller & Meyer, 2014), (b) the Neurosynth map corresponding to the term “language” (Yarkoni et al, 2011), and (c) a language ICN in control participants, obtained by placing a seed ROI within the left IFG (MNI coordinates −53 20 15).…”
Section: Methodssupporting
confidence: 62%
“…Within the RH, consistent patterns of connectivity were observed between the IFG and precentral gyrus, superior temporal sulcus, angular gyrus, temporal pole, left and, to a lesser extent, right cerebellum, and frontal pole. The analysis of the ICN obtained in neurotypical individuals demonstrated that the chosen ROI was effective at revealing the language network described in the previous studies (Muller & Meyer, 2014; Tie et al, 2014; Zhu et al, 2014). Thus, ROIs in the right IFG could be used as a starting point for exploring compensatory language networks in patients after hemispherectomy.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…Table 2. An alternative hypothesis to explain the bilateral plasticity in the AC in the present study can be supported by a growing body of research, suggesting that the apparent left-sided lateralization for speech and language processing, specifically in the AC, is not an absolute dominance but rather a shared expertise by the two hemispheres (79)(80)(81). The above hypotheses must be made with caution because at this premature age, cortical folding is still in flux and the majority of neurons are still migrating and have not yet reached their final cortical destination.…”
Section: Discussionmentioning
confidence: 50%